The cost–effectiveness of blue-light therapy in the treatment of mild-to-moderate psoriasis. (June 2017) - Ansaripour, Amir; Thio, Hok Bing; Maessen, Rob; Redekop, William Ken
Aim: To investigate the cost–effectiveness of blue-light therapy versus a two-compound formulation (TCF) (Dovobet ® gel [calcipotriol and betamethasone]) in mild-to-moderate psoriasis.Methods: A Markov model was applied to describe the course of disease among Dutch patients with a Psoriasis Area and Severity Index (PASI) score ≤ 10 over a 52-week time horizon. Patients received either 12-week blue-light therapy or two 4-week treatments with TCF. Patients, experiencing no PASI reduction after either therapy, were assumed to receive 12-week ultraviolet B phototherapy.Results: There was no significant difference in PASI reduction between two interventions (71 vs 72%). However, blue-light therapy was associated with a cost savings of EU€248.Conclusion: Treatment of mild-to-moderate chronic plaque psoriasis using blue-light therapy may be more cost-effective than TCF.